2014
DOI: 10.3233/bme-130814
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic parameters measurements to assess severity of serial lesions in patient specific right coronary artery

Abstract: In this study, effects of serial stenosis on coronary hemodynamics were investigated in the human right coronary artery (RCA) using blood flow analysis. A 3-D model of a serial stenosed RCA was reconstructed based on multislice computerized tomography images. Numerical analysis examined the effect of multiple serial stenoses on the hemodynamic characteristics such as flow separation, pressure drop and FFR. Pressure loss associated with flow expansion after each constriction was large. Overall pressure drop inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The magnitude of vorticity inherently depicts both the flow rate and its directional information. Previous studies have demonstrated that vorticity is relevant to turbulent flow as a result of lumen obstruction, local vessel expansion, or vessel motion; however, in these studies vorticity was assessed qualitatively rather than quantitatively (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of vorticity inherently depicts both the flow rate and its directional information. Previous studies have demonstrated that vorticity is relevant to turbulent flow as a result of lumen obstruction, local vessel expansion, or vessel motion; however, in these studies vorticity was assessed qualitatively rather than quantitatively (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, FFR had close and significant correlation with blood flow rate ( r = −0.995 and p = 0.005). This is because the curvilinear relation between flow increases and pressure loss (Figure ) . Holding other variable constant, higher flow rate led to higher pressure drop over the stenosis, which resulted in lower FFR.…”
Section: Resultsmentioning
confidence: 98%
“…These HPs include wall shear stress (WSS) , oscillatory shear index (OSI) , wall shear stress gradient (WSSG) , stress phase angle (SPA) , wall pressure, wall pressure gradient (WPG) and relative residence time (RRT) . In addition, CFD simulation on patient‐specific models has been explored to predict the clinical hemodynamic index of fractional flow reserve (FFR) for CAD diagnosis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exist two options for computation of the virtual FFR. The first option uses the 3D or 2D model of blood flow in the local region of the studied vessel [16,38,73,121,135,159,163,187] and suffers the bad posedness of upstream and downstream boundary conditions, rigid wall approximation for the vessel wall, high computational cost, local region for computational domain, difficulties in determining patient-specific parameters [140,181]. The recent trend is the use of machine learning tools for replacement of costly 3D simulations [45].…”
Section: Clinical Applicationsmentioning
confidence: 99%